The “real life” efficacy of dupilumab is independent of initial polyp size and concomitant steroids in CRSwNP - Nicholas J. Campion; Jonas Brugger; Aldine Tu; Victoria Stanek; Faris F. Brkic; Tina J. Bartosik; David T. Liu; Bruna S. Hoehl; Katharina Gangl; Julia Eckl-Dorna; Sven Schneider (Journal of Otolaryngology - Head and Neck Surgery, 2023)
Abstract Background Dupilumab significantly improves symptom control in chronic rhinosinusitis with nasal polyps (CRSwNP). Patients with large polyps at the initiation of treatment (total polyp score (TPS) ≥ 5) have been the focus in published studies. Patients with significant burden of disease but small polyps (TPS ≤ 4) have not yet been evaluated for clinical response. This study set out to evaluate the benefit of dupilumab treatment on cohorts of small (TPS ≤ 4) compared to large polyps (TPS ≥ 5). Furthermore, benefit of concomitant oral and/or nasal steroid therapy has been evaluated. Methods 97 patients with CRSwNP, who were begun on dupilumab between January 2020 and October 2021, were included. All patients were followed-up for 6 months. At each visit they underwent nasal endoscopy, smell identification tests and filled out validated patient questionnaires. Results Significant drops in TPS were seen in both patient groups after 6 months of therapy, dropping from a median score of 3 to 0 and from 6 to 2 in patients with small and large polyps respectively. Furthermore, a linear mixed model calculated a drop of 22% and 24% in TPS per month in patients with small and large polyps respectively with no significant difference in rate of decline. Finally the model showed that neither oral nor nasal steroids influenced the rate of response to dupilumab therapy. Conclusions Polyp size at the initiation of dupilumab therapy and whether patients continue to take steroid therapy does not appear to influence effectiveness of dupilumab treatment.